UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN INQUIRY LEARNING PADA SISWA KELAS XI-MIPA 5 DI SMAN 1 KAWEDANAN SEMESTER 2 TAHUN PELAJARAN 2019/2020 - Romlah (Pusat Studi Pendidikan dan Kreativitas Guru, 2020)
This study aims to determine the improvement of student learning outcomes by using the inquiry approach to the concept of acid-base solutions. Therefore, this study uses classroom action research. The research subjects were XI-MIPA 5 students at SMAN 1 Kawedanan, Magetan. The data obtained are in the form of student cognitive learning outcomes and student and teacher activities. Data on cognitive learning outcomes were obtained from the final cycle test, while student activities were obtained from observation sheets and field notes. Sources of data in this activity are students in the learning process. Student learning outcomes showed an increase with an average value in the first cycle of 75.15 and the second cycle of 80.74. With the percentage of the number of students who reached the KKM in the first cycle of 67.65% and the second cycle of 85.29% with success indicators of 75% of students who reached the KKM.